Living Collection Curation: A Holistic Approach, With the RBGE Palm House as a Case Study - Mitchell, David R (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2004)
The necessity to redesign and relandscape the interior of the Temperate Palmhouse at the Royal Botanic Garden Edinburgh (RBGE) created the opportunity to undertake a full curatorial survey of the palms and other plants contained in the Palmhouse. This paper gives the background to, and describes the process of, undertaking the survey. It stresses the need for maximum consultation with all interested parties to decide the fate of existing plants and make recommendations for new plantings. The result was a booklet describing the history and development of the Palmhouse, listings of all existing plants with notes on ethnobotanical use, value in teaching or research and final destination and suggestions for new species to meet the new design along with educational and interpretation opportunities. The resultant survey could act as a model for other projects.